Effect of Al doping on electrical properties of Si nanowire. (1st January 2014) - Kausar, Sana; Joshi, Shirish; Srivastava, Anurag
In this paper we present a theoretical study of the electron transport properties of Si nanowire and also the electron transport properties of nanowire doped with Al atoms by using Atomistix toolkit (ATK). The differences in the I-V curves obtained with each configuration and their technologic consequences are discussed in detail. ATK is a package which provides efficient calculations of materials transport properties and realistic device simulations to extract current-voltage and transfer characteristics. The simulation results were obtained using local density approximation based on density functional theory (DFT).